Digital Sociology : Critical Perspectives - Orton-Johnson, Kate (Palgrave Macmillan UK, 2017)
Sociology and our sociological imaginations are having to confront new digital landscapes spanning mediated social relationships, practices and social structures. This volume assesses the substantive challenges faced by the discipline as it critically reassesses its position in the digital age.